Application of Acoustic Radiation Force Impulse (ARFI) Elastography in Imaging of Delayed Onset Muscle Soreness (DOMS): A Comparative Analysis With 3T MRI - Hotfiel, Thilo; Kellermann, Marion; Swoboda, Bernd; Wildner, Dane; Golditz, Tobias; Grim, Casper; Raithel, Martin; Uder, Michael; Heiß, Rafael (Journal of Sport Rehabilitation, 2017)
DOMS is one of the most common reasons for impaired muscle performance in sports and is associated with reduced muscle strength and frequently observed both in professional and recreational athletes.To emphasize the diagnostic value of Acoustic Radiation Force Impulse (ARFI) in imaging of Delayed Onset Muscle Soreness by comparing findings to high-resolution 3T MRI T2 weighted sequences.Case series.Laboratory environment.Fifteen healthy students (7 female, 8 male, age 24 ± 4 years, height 178 ± 10 cm, body weight 67 ± 12 kg).ARFI values, represented as shear wave velocities (SWV) of the gastrocnemius muscle (GM) and soleus muscle (SM), as well as conventional ultrasound, high-resolution 3T MRI, creatine kinase activity, extension range of the ankle joint, calf circumference and muscle soreness were assessed before (baseline) and 60 hours after (post-intervention, PI) a standardized eccentric exercise.ARFI SWV values of the GM revealed a statistically significant decrease of 19.1% between baseline (2.2 ± 0.26 m/s) and PI (1.78 ± 0.24 m/s); p=0.008. At follow-up, the MRI investigations showed intramuscular oedema for the GM in all participants corresponding to a significant raise in T2 signal intensity (p=0.001) and in T2-time values (p=0.004).ARFI elastography seems to be an additional sensitive diagnostic modality in the diagnostic work up of DOMS. Intramuscular SWV could represent an additional imaging marker for the assessment and monitoring of ultrastructural muscle injuries and therefore be helpful for individual training composition in elite sports.
EVALuna2:10902